Peran Efektifitas Komunikasi Organisasi dalam Meningkatkan Motivasi Kerja Karyawan - Ni Kadek Suryani; Umaimah Wahid; Ahmad Toni (UNHI Press, 2023)
The purpose of this study is to see the similarity between the effectiveness of communication within the organization on employee motivation and the overall impact on employee performance. This study focuses on the fact that communication in the workplace can take many forms and has long-term effects on employee motivation, especially in the relationships between people in the organization. The method used in this study is a descriptive qualitative method with data collection techniques through literature studies using books, literature, scientific articles, or library materials. The results of the study show that the effectiveness of organizational communication is carried out through several stages which have a significant influence on employee motivation. The conclusion of the research is that a leader pays attention to important communication in the organization and minimizes the obstacles that occur so that communication goals and organizational goals can be achieved by increasing employee performance through work motivation.